Cardiac autonomic nerve function in polycystic ovary syndrome is not related to oxidative stress: A Poincaré analysis of heart rate variability - Mostafa, Musfika; Akhter, Ayesha; Sultana, Shamima; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2022)
Background: Polycystic ovary syndrome (PCOS) is a well recognized reproductive hormone disorder. It is often associated with dysautonomia and increased oxidative stress Objective: To assess the relationship between cardiac autonomic nerve function (CANF) and oxidative stress in patients with PCOS. Methods: This cross sectional study enrolled 30 newly diagnosed PCOS patients 20-35 years of age and 30 apparently healthy, regularly menstruating women of similar age and BMI. The patients were enrolled from outpatient Department of Endocrinology, BSMMU, Dhaka. CANF was assessed by poincare analysis of RR interval, a non linear method of Heart Rate Variability (HRV) analysis. HRV data of all subjects were recorded by a digital data acquisition device, Power lab 8/35, AD instruments, Australia, with lab chart software analysis. Oxidative stress was assessed by plasma catalase and plasma Malondialdehyde (MDA) levels. For statistical analysis unpaired “t” test and Pearson’s correlation test were used. Results: In this study, resting pulse rate, systolic blood pressure(SBP), diastolic blood pressure(DBP) were significantly higher (p<0.001, p<0.01, p<0.01 respectively) and standard deviation of the short term RR interval variability (SD1), ratio of short term and long term variability (SD1/SD2) ratio were significantly lower (p<0.001) in PCOS than those of healthy controls. In addition, plasma catalase levels was significantly lower (p<0.01) and plasma MDA levels was significantly higher (p<0.001) in PCOS patients compared to controls. On correlation analysis, SD1 showed negative correlation with plasma catalase and plasma MDA levels (p>0.05) in PCOS patients. In addition SD1/SD2 ratio showed positive correlation with plasma catalase and negative correlation with plasma MDA levels (p>0.05) in these group of patients. But all these correlations were statistically not significant. Conclusion: The present study reveals association of autonomic dysfunction and higher oxidative stress with PCOS but it failed to show evidence for any interrelationship between them. J Bngladesh Soc Physiol 2021;16(1): 88-94